An Experimental Approach for Understanding V-I Characteristic of Electric Arc Furnace Load - Seker, Mustafa; Memmedov, Arif (Elektronika ir Elektrotechnika, 2017)
Electric Arc Furnaces (EAF) are nonlinear loads causing power quality problems on the systems they are connected to. The main reason of EAFs causing power quality problems is the nonlinear characteristics of the electric arc. In this study, dynamic working characteristics of electric arc furnace load at Sivas Iron and Steel Incorporated Company (SIDEMIR) operating with 60 MVA EAF have been experimentally examined by HIOKI 3197 PQ analyser. Utilizing the measured dynamic load curves, mathematical equation and proper parameters have been determined for modelling electrical arc with the help of curve fitting methods on Matlab program. Also by modeling a phase equivalent of the system and harmonic filters existing on the system, a time domain model has been formed and with this model, harmonic effects of the EAF have been examined with Matlab/Simulink. Simulation results show that the presented model can be used for examining PQ and voltage harmonics problems caused by EAF loads.DOI: http://dx.doi.org/10.5755/j01.eie.23.3.18328